2016
DOI: 10.1038/srep36768
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel MYO18A interaction partners required for myoblast adhesion and muscle integrity

Abstract: The unconventional myosin MYO18A that contains a PDZ domain is required for muscle integrity during zebrafish development. However, the mechanism by which it functions in myofibers is not clear. The presence of a PDZ domain suggests that MYO18A may interact with other partners to perform muscle-specific functions. Here we performed double-hybrid screening and co-immunoprecipitation to identify MYO18A-interacting proteins, and have identified p190RhoGEF and Golgin45 as novel partners for the MYO18A PDZ domain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
1
15
0
1
Order By: Relevance
“…These imply that Lurap1 regulates microtubule cytoskeleton organisation in a similar manner as Wnt/PCP signalling. However, we could not at present exclude the possibility that Lurap1 regulates cell polarity independently of Dvl since it also interacts with other proteins such as MRCK and MYO18A that play a role in cell adhesion and migration 40 , 41 . In addition, it is well established that Wnt/PCP signal is transduced via Dvl to the small GTPases Rac and Rho, which activate distinct downstream effectors to modulate the actin cytoskeleton 33 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These imply that Lurap1 regulates microtubule cytoskeleton organisation in a similar manner as Wnt/PCP signalling. However, we could not at present exclude the possibility that Lurap1 regulates cell polarity independently of Dvl since it also interacts with other proteins such as MRCK and MYO18A that play a role in cell adhesion and migration 40 , 41 . In addition, it is well established that Wnt/PCP signal is transduced via Dvl to the small GTPases Rac and Rho, which activate distinct downstream effectors to modulate the actin cytoskeleton 33 .…”
Section: Discussionmentioning
confidence: 91%
“…Lurap1 (leucine repeat adaptor protein 1), also known as Lrap35a, is an adaptor protein with two leucine-rich repeats at its N-terminal region and a PDZ-binding motif at the extreme C-terminus 40 . In cultured cells, it has been shown that Lurap1 regulates actomyosin retrograde flow and cell migration by forming a tripartite complex with myotonic dystrophy kinase-related Rac/Cdc42-binding kinase (MRCK), and the unconventional MYO18A through the leucine-rich repeats and the PDZ-binding motif, respectively 40 , 41 . Although this protein is highly conserved among vertebrate species, its implication in regulating cell movements during early development has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Because it is the only myosin-18 in Drosophila , this observation did not provide a clear clue whether myosin-18A is functioning in muscle in vertebrates. There were two consecutive studies in zebrafish that revealed the role of myosin-18A in striated muscle development and function ( Cao et al, 2014 , 2016 ). Two myosin-18A genes MYO18Aα and MYO18Aβ exist in zebrafish, and both of them were expressed in somites during muscle development, and knockdown of MYO18A , as well as overexpression of the PDZ domain disrupted myofiber integrity ( Cao et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish, gene duplication gave rise to two MYO18A genes, myo18aa and myo18ab. In a pair of publications, Cao et al have studied the function of the two MYO18A genes in zebrafish (Cao et al, 2014, 2016). Using in situ hybridization they detected ubiquitous expression of both genes, with enrichment in the somites.…”
Section: Function Of Myo18a In Model Organismsmentioning
confidence: 99%